Efficient and Compact Diode-Pumped Nd:YAG Lasers at 1073 and 1078 nm - Zhi Lin; Xiaoxu Huang; Jinglong Lan; Yongjie Cheng; Yi Wang; Bin Xu; Huiying Xu; Zhiping Cai (IEEE Photonics Journal)
We report on the efficient diode-pumped continuous-wave laser operation of a Nd:YAG crystal at several wavelengths by using a simple and compact two-mirror laser cavity and an undoped YAG thin plate acting as a Fabry-Pérot (F-P) etalon. We thus obtain a high-power single-wavelength laser operation at about 1073 nm with a maximum output power of 5.58 W and a laser slope efficiency of about 36.6%, with respect to absorbed pump power, which is believed to be the highest output power ever obtained with Nd:YAG at 1073 nm. We also achieve dual-wavelength laser operation at 1064 and 1078 nm, with a maximum output power of 1.57 W, and triwavelength laser operation at 1061, 1064, and 1078 nm, with a maximum output power of 2.16 W. This is the first demonstration, to the best of our knowledge, of a diode-pumped Nd:YAG laser at 1078 nm.